Social accounting in supply chain management: a pragmatic constructivist perspective - Pianezzi, Daniela; Cinquini, Lino (Proceedings of Pragmatic Constructivism, 2015)
This study explores the role of accounting in the human rights management within the supply chain.Our interest for this issue arises from the recognition of significant changes occurred in the last decades. In today’s global economy, “the competition has shifted more and more from an inter-firm to an inter-supply-chain level” (Gold et al., 2010) and many organizations are part of one or more supply chains (Samaranayake, 2005). As a result, “management processes now quite frequently transcend legal organizational boundaries” (Hopwood, 1996), as well as production processes. The financial crisis has emphasized the shift of power from nation states to transnational corporations at the centre of global value chains. These powerful actors are increasingly challenged by human rights violations occurring in the socio-political contexts in which they operate (Ruggie, 2007), especially where national law does not provide adequate protection. In these growing network systems, the main difficulty for a focal company is to exercise management control on suppliers over which it has no ownership, but for the behaviour of which it is held accountable (Andersen and Skjoett-Larsen, 2009). Indeed, in 2011, for the first time in the history, the UN Special Representative, John G. Ruggie, declared that corporations have direct human rights responsibilities, either through their own activities or as a result of their business relationships with other parties.